Filipe Alves Moreira & João Paulo Martins Ferreira, Livro de Linhagens do Deão, «Portugaliae Monumenta Historica, Nova Série, Volume XI», Lisboa, Academia das Ciências, 2019-2020. - Leite, Mariana (Guarecer. Revista Eletrónica de Estudos Medievais, 2024)
DOI: 10.21747/21839301/gua6ap